THE JOINT COMPREHENSIVE PLAN OF ACTION (JCPOA): RESULTS AND ACHIEVEMENTS - Mehdi Khazaie, Mousa Mousavi Zanouz, Hassan Soleimani (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
With the victory of the Islamic Revolution and its goal of achieving the comprehensive development of nuclear energy again, it became the focus of the men of the government of the Islamic Republic of Iran. Enmity with the Islamic Revolution and opposition to the West with its development caused Iran's goal of peaceful use of nuclear energy to turn into an international crisis and lead to the formation of opposition to Iran's progress in this area contrary to international standards, especially the IAEA. This process of nuclear conflict continued for a long time until it was finally concluded in the form of the Borjam Agreement between Iran and the P5 + 1. The present study is a descriptive-analytical method with the method of libraries with taking notes of law book sources and also using Internet resources are used to examine the legal implications of JCPOA. Therefore, in this study, while examining the history of Iran's nuclear program, the historical course of the nuclear negotiations from the 2000s to the Vienna Agreement, the legal opportunities and threats of the IAEA, the legal weakness of the IAEA and the US withdrawal from the IAEA as a political agreement and consequences Its political and economic issues were addressed. Some believe that after reaching a nuclear agreement or a UN Security Council, due to the form of the document and citing the intentions of the parties and explicitly the text, only the executive document contains some voluntary action by both parties and therefore, it can not be A treaty, agreement, treaty or international agreement